Charles Darwin on Volcanoes - Geist, Dennis; Gibson, Sally (Volcanica, 2025)
During the voyage of the H.M.S. Beagle (1831–1836), Charles Darwin had the opportunity to visit and observe volcanoes and volcanic deposits at several archipelagos in the Atlantic, Pacific, and Indian Oceans and also in the Andes. In the Galápagos Archipelago, he described hydrovolcanism and what we now know as pyroclastic surge deposits. Darwin also noted the relation between scoria and lava in Strombolian deposits and the role of effective viscosity on lava surface morphology. He observed volcanic eruptions in the Andes from a distance and speculated on the role of earthquakes in triggering eruptions. Darwin's field work on Ascension, the Cape Verde Islands, Mauritius, and the Azores included detailed work on volcanic bombs and the spatial relationship between basalt and evolved lavas. Much of his focus was on making detailed observations at the outcrop scale to deduce large-scale geologic processes, such as the relation between magmatism and mountain building and the distribution of magma in the deep Earth. While many of Darwin's theories involving volcanism did not stand the test of time, in contrast to his theories on coral reefs and the origin of species, they exemplify his genius at developing novel hypotheses and making observations to test those hypotheses.